TINJAUAN PENGISIAN RESUME KELUAR RAWAT INAP RUANG TERATAI TRIWULAN IV DI RSUD KABUPATEN CIAMIS TAHUN 2012 - Irmawati Irmawati; Lily Kresnowati; Edy Susanto; Teni Ikhsan Nurfalah (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2014)
ABSTRACTThis study aims to review the completeness and incompleteness resume filling out the form in the Lotusroom because it has the largest number of patients. The content of completeness reviewed in this study areidentification, important statement and authentication. Outcome resume has an important role as a meanof communication between physicians and other officers, the underlying planning of patient care, enablingmaterial analysis and evaluating quality of patient care, a legal document as patient needs, hospitals anddoctors, generating clinical data for research and education as well as providing information to the insuranceor any other payments. Therefore, the completeness of filling outcome resume is important. This study usesdescriptive analysis to do observations. Observations made on secondary data then processed to producequantitative data. The results showed that the completeness of outcome resume content identification form asmuch as 97.93%, significant report as much as 89.44% authentication as much as 96.00%and correct reportas much as 97.48%. From these results it can be concluded that the completeness of the whole elements rangefrom 94, 61%. Refers to the minimal standard documents which proposed the health department in 2007,that the documents should be 100%. It can be concluded that outcome resume in Ciamis District Hospital isincomplete filling.Keywords: Completed Outcome Resume